Pengaruh Efikasi Diri, Komunikasi Matematika, Dan Keterampilan Berhitung Terhadap Kemampuan Pemecahan Masalah Matematika Peserta Didik Kelas I SD Di Gading Serpong, Tangerang - Vera Eunike S; Laurens Kalug (Journal on Education, 2024)
Mathematics is a fundamental science needed in daily life. However, in practice, learners often encounter difficulties in applying mathematics to solve mathematical problems. Learners require self-efficacy to build confidence and resilience in overcoming mathematical challenges. Mathematical communication provides learners with the ability to express mathematical ideas, enabling them to find solutions to mathematical problems. Additionally, calculation skills are essential for learners in operating numbers to obtain calculated results for mathematical problems. This research aims to examine the influence of self-efficacy, mathematical communication, and calculation skills on the ability to solve mathematical problems in first-grade elementary school students. A quantitative study was conducted with 75 first-grade students. To measure learners' self-efficacy, a questionnaire with 30 questions was used. Three dimensions, namely magnitude, strength, and generality, were employed to measure learners' beliefs, resilience, and perseverance in addressing given mathematical problems. A mathematical story problem, along with three criteria: mathematical communication, calculation skills, and the ability to solve mathematical problems, was also provided to research respondents. Regression analysis revealed that self-efficacy, mathematical communication, and calculation skills significantly influence the ability to solve mathematical problems. Based on the research findings, measures were determined to enhance the problem-solving skills of first-grade elementary school students.